2006
DOI: 10.1038/sj.onc.1210126
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the zinc-finger protein 217 transcriptional repressor complex: identification of a ZNF217 consensus recognition sequence

Abstract: Zinc-finger protein 217 (ZNF217) is a Kruppel-like zincfinger protein located at 20q13.2, within a region of recurrent maximal amplification. Here, we demonstrate that ZNF217 is a transcriptional repressor protein and report the purification and characterization of a ZNF217 complex. The purified ZNF217 complex consists of approximately six proteins and contains the transcriptional co-repressors CoREST, BHC110/LSD1, histone deacetylase (HDAC) 2 and C-terminal binding protein (CtBP1). The purified ZNF217 complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 27 publications
4
111
0
Order By: Relevance
“…We began by investigating how ZNF217 might localize to the E-cadherin promoter and confirmed the previous observation that only fingers 6 and 7 detectably contact DNA (29). However, our results suggested that the E-cadherin site was bound with low affinity, prompting further mapping and mutagenesis experiments to search for higher affinity recognition sites.…”
mentioning
confidence: 48%
See 3 more Smart Citations
“…We began by investigating how ZNF217 might localize to the E-cadherin promoter and confirmed the previous observation that only fingers 6 and 7 detectably contact DNA (29). However, our results suggested that the E-cadherin site was bound with low affinity, prompting further mapping and mutagenesis experiments to search for higher affinity recognition sites.…”
mentioning
confidence: 48%
“…To identify the domain(s) responsible for DNA recognition, we first expressed the various zinc finger clusters as GST fusion proteins in bacteria and purified them by glutathione affinity chromatography. Recent work has suggested that ZNF217 binds a particular cis-element, CAGAAC, in the human E-cadherin promoter (29). We tested various zinc finger combinations of both mouse and human ZNF217 with this element in an EMSA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some ZFPs function as oncogenic proteins such as ZNF217 and ZNF639 (1,2), whereas others can act as tumor suppressors, such as ZAC, ST18, and ZNF382 (3)(4)(5). ZFPs bind to promoters with their zinc finger domains and activate or repress gene expression through their association proteins (1,6).…”
Section: Introductionmentioning
confidence: 99%